Elastin-like Polypeptides in Development of Nanomaterials for Application in the Medical Field - Lima, Letícia Ferreira; Sousa, Mauricio Gonçalves Da Costa; Rodrigues, Gisele Regina; de Oliveira, Kamila Botelho Sampaio; Pereira, Ana Margarida; da Costa, André; Machado, Raul; Franco, Octavio Luiz; Dias, Simoni Campos (Frontiers in Nanotechnology, 2022)
Elastin-like polypeptides (ELPs) are biopolymers formed by amino acid sequences derived from tropoelastin. These biomolecules can be soluble below critical temperatures, forming aggregates at higher temperatures, which makes them an interesting source for the design of different nanobiomaterials. These nanobiomaterials can be obtained from heterologous expression in several organisms such as bacteria, fungi, and plants. Thanks to the many advantages of ELPs, they have been used in the biomedical field to develop nanoparticles, nanofibers, and nanocomposites. These nanostructures can be used in multiple applications such as drug delivery systems, treatments of type 2 diabetes, cardiovascular diseases, tissue repair and cancer therapy. Thus, this review aims to shed some light on the main advances in elastin-like-based nanomaterials, their possible expression forms and importance to the medical field.